Causal mechanisms and evolution processes of “block-burst” debris flow hazard chains in mountainous urban areas: a case study of Meilong gully in Danba county, Sichuan Province, China - Shen, Haowen; Yang, Zhiquan; Hu, Guisheng; Tian, Shufeng; Rahman, Mahfuzur; Ren, Jincheng; Zhang, Yong (Frontiers in Earth Science, 2024)
On June 17, 2020, at approximately 3:20 am, a debris flow occurred in Meilong gully (MLG), located in Banshanmen Town, Danba County, in southwest China’s Sichuan Province. The debris flow had a discharge volume of approximately 40 × 104 m3 and rushed out to block the Xiaojinchuan (XJC) river, subsequently forming a barrier lake. This event ultimately induced a hazard chain that included heavy rainfall, debris flow, landslides, the formation of a barrier lake, and an outburst flood. The impact of this chain resulted in the displacement of 48 households and affected 175 individuals. Furthermore, it led to the destruction of an 18 km section of National Highway G350, stretching from Xiaojin to Danba County, causing economic losses estimated at 65 million yuan. The objective of this study is to analyze the factors leading to the formation of this hazard chain, elucidate its triggering mechanisms, and provide insights for urban areas in the western mountainous region of Sichuan to prevent similar dam-break type debris flow hazard chains. The research findings, derived from field investigations, remote sensing imagery analysis, and parameter calculations, indicate that prior seismic disturbances and multiple dry-wet cycle events increased the volume of loose solid materials within the MLG watershed. Subsequently, heavy rainfall triggered the initiation of the debris flow in MLG. The cascading dam-break, resulting from three unstable slopes and boulders within the channel, amplified the scale of the hazard chain, leading to a significant amount of solid material rushing into the XJC river, thus creating a dam that constricted the river channel. With the intensification of river scouring, the reactivation and destabilization of the Aniangzhai (ANZ) paleolandslide occurred, ultimately leading to the breach of the dam and the formation of an outburst flood. The research comprehensively and profoundly reveals the causal mechanism of the MLG hazard chain, and proposes measures to disrupt the chain at various stages, which can aid in enhancing monitoring, early warning, forecasting systems, and identifying key directions for ecological environmental protection in urban areas within the western mountainous region of Sichuan.